Enhanced catalytic ozonation of ibuprofen using a 3D structured catalyst with MnO2 nanosheets on carbon microfibers - Guhankumar Ponnusamy (Nature Portfolio, 2021)
Abstract Heterogeneous catalytic ozonation is an effective approach to degrade refractory organic pollutants in water. However, ozonation catalysts with combined merits of high activity, good reusability and low cost for practical industrial applications are still rare. This study aims to develop an efficient, stable and economic ozonation catalyst for the degradation of Ibuprofen, a pharmaceutical compound frequently detected as a refractory pollutant in treated wastewaters. The novel three-dimensional network-structured catalyst, comprising of δ-MnO2 nanosheets grown on woven carbon microfibers (MnO2 nanosheets/carbon microfiber), was synthesized via a facile hydrothermal approach. Catalytic ozonation performance of Ibuprofen removal in water using the new catalyst proves a significant enhancement, where Ibuprofen removal efficiency of close to 90% was achieved with a catalyst loading of 1% (w/v). In contrast, conventional ozonation was only able to achieve 65% removal efficiency under the same operating condition. The enhanced performance with the new catalyst could be attributed to its significantly increased available surface active sites and improved mass transfer of reaction media, as a result of the special surface and structure properties of this new three-dimensional network-structured catalyst. Moreover, the new catalyst displays excellent stability and reusability for ibuprofen degradation over successive reaction cycles. The facile synthesis method and low-cost materials render the new catalyst high potential for industrial scaling up. With the combined advantages of high efficiency, high stability, and low cost, this study sheds new light for industrial applications of ozonation catalysts.